THE USE OF COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH TO TEACH SPEAKING RECOUNT TEXT TO EIGHT GRADE STUDENTS OF SMPN 2 JOMBANG (RETAIN, 2014)
THE USE OF COMMUNICATIVE LANGUAGE TEACHING (CLT) APPROACH TO TEACH SPEAKING RECOUNT TEXT TO EIGHT GRADE STUDENTS OF SMPN 2 JOMBANG Ratna Sari S1- English Education, Language and Art Faculty, Surabaya State University, Anna.sweet9ty1@gmail.com Esti Kurniasih, S.Pd., M.Pd English Department, Languages and Arts Faculty, State University of Surabaya estikurniasih87@yahoo.com Abstrak Keterampilan berbicara merupakan bagian penting dari proses mengajar dan belajar bahasa asing karena pelajar perlu menguasai keterampilan ini agar mampu berkomunikasi di kehidupan sehari-hari.Akhir-akhir ini, di Indonesia, pengajaran dan pembelajaran bahasa inggris hanya memfokuskan pada dril pengulangan atau menghafal dialog. Dengan pembelajaran seperti ini, guru hanya memberikan pengetahuan dasar dengan melakukan dril pengulangan dan menghafal dialog. Cara pembelajaran bahasa inggris seperti ini tidak dapat mencapai tujuan daripada pembelajaran berbicara yang mana harapannya siswa dapat berkomunikasi dalam kehidupan sehari-hari dengan menggunakan bahasa tersebut. Selain itu, banyak guru bahasa inggris yang memberikan sedikit kesempatan kepada siswa untuk berbicara di kelas. Oleh sebab itu, siswa terkadang pasif dan tidak termotivasi dalam pembelajaran keterampilan berbicara karena guru mereka mendominasi untuk berbicara di kelas. Olehkarena itu, guru perlu untuk menerapkan sebuah pendekatan pembelajaran dalam pengajaran keterampilan berbicara. Secara mendasar, ada beberapa pendekatan pembelajaran yang dapat diterapkan dalam pengajaran keterampilan berbicara. Salah satunya adalah penggunaan pendekatan pembelajaran Communicative Language Teaching (CLT).Pendekatan pembelajaran Communicative Language Teaching (CLT)adalah suatu pendekatan pembelajaran yang mana bahasa dipelajari dengan mengkomunikasikannya secara langsung. Pendekatan pembelajaran Communicative Language Teaching (CLT) menyediakan beberapa aktivitas yang dapat membuat siswa lebih aktif berbicara di kelas. Adapun tujuan daripada penelitian ini adalah mendeskripsikan penerapan penggunaan pendekatan pembelajaran Communicative Language Teaching (CLT)untuk pengajaran keterampilan berbicara teks Recount, respon siswa terhadap penerapan penggunaan pendekatan pembelajaran Communicative Language Teaching (CLT)untuk pengajaran keterampilan berbicara teks Recount, dan hasil dari tugas keterampilan berbicara siswa selama penerapan penggunaan pendekatan pembelajaran Communicative Language Teaching (CLT)untuk pengajaran keterampilan berbicara teks Recount pada siswa kelas VIII SMPN 2 Jombang. Peneliti menggunakan deskriptif kualitatif dalam penelitian ini. Peneliti menggunakan observation check list, field note, and closed- structured questionnaire sebagai instrumen dalam pengumpulan data dan mendeskripsikan data yang didapat secara deskriptif. Hasil daripada penelitian ini menunjukkan bahwa guru membuat siswa lebih aktif berbicara dengan jalan memberi beberapa pertanyaan kepada siswa secara oral lalu mereka secara bergantian menjawab pertanyaan tersebur secara oral juga. Selain itu, peneliti juga meminta mereka untuk melakukan percakapan dengan teman sebangkunya tentang kegiatan yang mereka lakukan di waktu lampau. Selain itu, berdasarkan hasil kuesioner siswa, mereka berpendapat bahwa penerapan penggunaan pendekatan pembelajaran Communicative Language Teaching (CLT)untuk pengajaran keterampilan berbicara teks Recountmenarik dan membuat mereka lebih aktif di kelas. Selain itu, hasil dari tugas keterampilan berbicara siswa menunjukkan bahwa siswa dapat menyampaikan pidato dengan baik secara oganisasi, kelancaran, pelafalan, kosakata, dan penampilan. Hasil dari penelitian ini dapat disimpulkan bahwa pendekatan pembelajaran Communicative Language Teaching (CLT) membuat siswa lebih aktif di kelas. Abstract Speaking is considered as a crucial part of foreign language teaching and learning because English learners need to master it in order to be able to communicate in real life. Nowadays, in Indonesia, teaching and learning speaking simply focuses on repetition of drills or memorization of the dialogue. It seems that teacher only gives such kind of surface knowledge by doing repetition of drills or just memorizing the dialogue. The way of teaching by focusing on drills and memorizing the dialogue will not achieve the goal of teaching speaking in which students are expected to be able to communicate using the language in real life. Besides, English teachers also commonly give little chance for students to speak more in the class. As a result, students sometimes are passive and unmotivated in speaking activity because their teachers dominate to speak more in the class. Therefore, the teacher needs to apply an approach to teach speaking. Basically, there are some approaches that can be used to teach speaking. One of them is Communicative Language Teaching Approach. Communicative Language Teaching (CLT) approach is a teaching approach which language is taught in communicative way. It can be said that CLT approach provides some activities that can encourage the students to speak more in the class. The aim of this study was to describe the use of CLT approach to teach speaking Recount Text, the students’ responses toward the implementation of CLT approach to teach speaking Recount Text, and the students’ speaking result during the implementation of CLT approach to teach speaking Recount Text to eight graders of SMP Negeri 2 Jombang. The researcher used a descriptive qualitative research in conducting this study. She used observation check list, field note, and closed- structured questionnaire as the instruments to collect the data and described the data got in descriptive way. The result showed that the teacher encouraged the students to speak up in the class by asking them some questions then they answered them orally. Besides, she also had them do a conversation with their friends about their past activity. In addition, the students’ responses showed that CLT approach was interesting and made them more active in the class. Furthermore, the result of the students’ recount speaking task showed that most of the students were able to deliver their recount speech well in term of their organization, fluency, pronunciation, vocabulary, and performance. In conclusion, the use of CLT approach could make the students more active in the class because it contains some activities that encourage the students to speak up in the class. Key words: speaking, teaching speaking, CLT approach and Recount Text. INTRODUCTION Speaking is classified as a productive skill which takes an important role in mastering English. As productive skill, speaking becomes a measurement whether learners have mastered English or not. As stated by Richards (2008), English learners evaluate their success in learning language by knowing how much they feel that they have improved in their spoken language proficiency. In this case, learners will think whether they have mastered the language or not by measuring their spoken ability in using the language itself. In addition, speaking is considered as a crucial part of second language teaching and learning (Kayi, 2006) because English learners need to master it in order to be able to communicate in real life. Nowadays, in Indonesia, teaching and learning speaking simply focuses on repetition of drills or memorization of the dialogue (Kayi, 2006). It seems that teacher only gives such kind of surface knowledge by doing repetition of drills or just memorizing the dialogue. Basically, language is taught through communicative interaction between teacher and students. The way of teaching by focusing on drills and memorizing the dialogue will not achieve the goal of teaching speaking in which students are expected to be able to communicate using the language in real life. One of the examples of the activity that is usually done by English teachers in Indonesia is when the teacher asks the students to make a dialogue in pair. The teacher just asks the students to make a dialogue with their friends and gets them to memorize the dialogue. After that, the teachers let them have a conversation in front of the class. As a result, students seem as if they have a good conversation, but, in fact, they are still unable to speak in real life situation. Besides, English teachers also commonly give little chance for students to speak more in the class. Teachers seem often dominate to speak more in the class. As a result, students sometimes are passive and unmotivated in speaking activity because their teachers dominate to speak more in the class. In short, from those problems that commonly happen in the process of teaching and learning speaking, the main problem which makes the students prefer to be silent and do not have any enough chances to speak up is an appropriate approach that is used by the teachers in teaching speaking. Communicative Language Teaching (CLT) is one of the teaching approaches which emphasizes on language use rather than on language as structure (Hossen, 2008). In other words, CLT concerns more on how language is used to communicate than on how language is produced correctly. Finocchiaro and Brumfit (1983) also said that communicative language teaching is a teaching approach which language is taught in communicative way. It means that learners learn language through communication. In communicative language teaching, learners learn language by using it in real communication. Therefore, in communicative language teaching, classroom activities should be meaningful and involve real communication. It is also supported by Littlewood (1981) in Hossen (2008) who stated that CLT serves some activities which learners are able to use the language appropriately in a given social context. CLT approach has some principles or basic features. Hossen (2008) said that there are ten basic features of CLT approach such as emphasizing the importance of language as a tool for communication rather than a subject to be studied, using real life language in situations rather than only learning grammatical rules, using the language needs of the learner as the basis for the syllabus, balancing between fluency and accuracy as a goal of learning, concerning for the appropriate use of language according to the situation, applying various type of materials in the classroom, using dialogues as tool of learning, emphasizing four skills (listening, speaking, reading, and writing) to be learned, consisting scope of variety and innovations in the classroom and making the lesson interesting. According to Littlewood (1981), there are two main activities which are conducted in CLT approach namely functional and social communication activities. In functional activities, the teacher conducts activity that can promote the students to speak up in the class. Beside, according to Littlewood (1981), functional activities require the students to use their language resources to give information to others. So in this case, the teacher conducts conversation with the students in order to get information from them. Functional communication activities aim to develop certain language skills and functions that involve communication (Littlewood, 1981). Meanwhile, in social interaction activities, the teacher has the students make a conversation with their friends since the aim of these activities is to make the students are able to learn language in social context by doing conversation with their friends. METHOD The aim of this study was to describe the use of CLT approach to teach speaking Recount Text, the students’ responses toward the implementation of CLT approach to teach speaking Recount Text, and the students’ speaking result during the implementation of CLT approach to teach speaking Recount Text to eight graders of SMP Negeri 2 Jombang. In line with the aim of the study above, a descriptive qualitative research was used in this study. Since this study belongs to descriptive qualitative research, the writer did not take any parts in the activities. What the writer did after stating the research questions was observing and taking note of the activities of the teacher and the learners in class and also the approach used by the teacher during the observation instead. She conducted the research in three times. They were on 19th, 26th of November, and 02ndof December 2013..Then, at the end of meeting, the researcher asked the students to perform monologue recount text. The students told about their past experience Furthermore, the instruments that the researcher used to collect the data were observation check list, field-note, closed-structured questionnaire, and students’ recount monologue speech result. The observation check list and field-notes were used as the instruments to answer the first research question. . The observation check list is in the form of yes and no answer. In addition, the observation checklist contains the teacher’s activities, the students’ activities, the learning material, and the approach which were applied. While, the field note is in the form of word or sentence, so the researcher took a note on the activities from the beginning until the end of the class. During observation, the researcher wrote the descriptive and reflective part. In this study, the researcher used closed-structured questionnaire. It was used to collect the data about the students' responses toward the implementation of CLT approach in teaching speaking recount text. The questionnaire was given at the end of the observation so that students could answer all the questions. The questionnaire used in this research consists of 11 questions. To obtain the data dealing with the students’ speaking ability during the implementation of CLT approach to teach speaking recount text, the students’ task was given. The students’ task was given on the fourth meeting. The students’ task was in the form of monologue speech of recount text. After collecting all of the data which were gotten from the observation checklist, field-note, closed-structure questionnaire, and students’ recount monologue speech result, the researcher then analyzed them descriptively. In analyzing the data of this research, the researcher did three concurrent flows of activities namely data reduction, data display, and conclusion drawing/ verification (Miles and Huberman, 1994 in Koshy, 2005). RESULTS AND DISCUSSION Results The researcher did the observation for three days, on Tuesday November 19th, Tuesday November 26th, and Monday December 2nd 2013. On the first meeting, the teacher applied the CLT approach to teach speaking recount text in the class. She asked one of the students to retell activity that she or he did last Sunday. Then she or he retold it orally. After that, the teacher asked some questions to other students in the class toward the story. Then they answered the questions orally. Next, the teacher showed a video about her activity on last Sunday. After the video was played, she gave some questions toward the content of the video. Then the students answered those questions orally. Then the teacher asked the students to have a conversation with their friend. The conversation was like an interviewing activity. The students had to ask their friend about activity that she or he did on last Sunday. After they had conversation, they presented the result of their interview in front of the class. The teacher gave some comments toward the result of the students’ interview. On the second meeting on November 26th 2013, the teacher did the same activity at the beginning of the lesson. Then she asked one of the students who joined leadership activity to tell what he did on the event. Then he told his activities when joining the event orally. After that, the teacher reviewed the story that was just told by the student by delivering some questions related to the story. Then the students actively answered those questions. The activities that were done by the teacher in the class like asking the students to tell their past experience, and delivering some questions to be answered by the students orally are able to make the students engage in communication. On the third meeting on November 2nd 2013, the teacher reviewed the previous explanation about recount text. She asked some questions about recount text material to the students. After that, the teacher showed power point slides which contains story about my mother. Each slide shows a sentence which describes a mother story. After showing it, the teacher asked the students about what the power point slide tells about. So in this part, the teacher taught speaking to the students because the teacher practiced speaking with the students by asking them some questions. Then the students answered it orally. Discussion The Implementation of CLT Approach in Teaching Speaking Recount Text to the Eight Grade Students of SMPN 2 Jombang Based on the result of three meetings on November 19th, 26th and December 2nd, 2013, it can be seen that the implementation of CLT approach can help the students encourage the acquisition of communication skill and foster real communication (Murcia, 1991). In addition, it can also help the students to achieve communicative competence (Richards, 2006). On the first meeting on November 19th 2013, the teacher did such kind of brainstorming to attract the students’ attention toward the lesson that they would learn. She asked one of the students to tell his past experience. The student told his activity on last Sunday orally. The way how the teacher asked the student to tell his experience was by conducting conversation with him. After that, she reviewed the story that was just told by the students by delivering some questions related to the story. Then the students actively answered those questions. Sometimes in answering those questions, some students produced mistake on grammar but the teacher did not pay attention more on it. She just corrected the mistake that was produced by the student. The teacher paid attention more on the language rather than on grammar (Hossen, 2008). Next, the teacher played a video which contains the teacher’s activity on last Sunday. She asked the students to note down some important things on the video. After that, she gave some questions which were about the story on the video. The teacher delivered the questions orally. As stated by Littlewood (1981), CLT approach should provide an activity which promotes the students to speak up in the class. One of the activities that can be done is by playing the video then the students are given some questions toward the video. Then the students tried to be active in the class by answering those questions orally. In this case, it can be seen that the way how the teacher taught English language was in communicative way. Since in CLT approach the language is taught in communicative way (Finocchiaro and Brumfit, 1983), the teacher tried to make the students speak up by giving them some questions then the students tried to answer them orally. Then the teacher gave detail explanation about recount text. It was about the definition of recount text, generic structure of recount text, tense that is used in recount text, and so on. After that, the teacher asked the students to have a conversation or dialogue with their friend. Since dialogues are used as tool of learning in CLT (Hossen, 2008), the teacher asked the students to do a conversation. Furthermore, as stated by Larsen-Freeman (1986), the teacher is as a co-communicator whose duty is to establish situations that prompt communication between and among the students in CLT approach. They got task to interview their friend about their activity on last Sunday. In this activity, the teacher wanted to create a real situation in the class in order to make the students able to speak in real communication. In CLT approach, classroom activities should be meaningful and involve real communication. It is also supported by Littlewood (1981) in Hossen (2008) who stated that CLT serves some activities which learners are able to use the language appropriately in a given social context. Furthermore, the reason that made the teacher ask the students to make a conversation because she wanted the students can learn language through interaction (Banciu&Jireghie, 2012). On the second meeting on November 26th 2013, the teacher did the same activity at the beginning of the lesson. Then she asked one of the students who joined leadership activity to tell what he did on the event. Then he told his activities when joining the event orally. After that, the teacher reviewed the story that was just told by the student by delivering some questions related to the story. Then the students actively answered those questions. The activities that were done by the teacher in the class like asking the students to tell their past experience, and delivering some questions to be answered by the students orally are able to make the students engage in communication. As stated by Richards & Rodgers (1999), classroom activities in CLT approach should make the learners engage in communication. On the second meeting, the teacher did not only teach speaking to the students but also teach writing. However, the teacher concerned more on the students’ speaking. After the teacher had conversation with the student, the teacher had the students gather in their group. Each group consists of four people. The teacher instructed each group to choose one of their friends to be a writer. The teacher asked the students to make a recount text in a group. She has already chosen the topic to be discussed. While the students were doing their task in group, she guided them. She asked the students to start their story with orientation. They discussed and cooperated with their friends to create the story. After they finished it, the teacher asked them to present their story in front of the class. Two representative students of each group came to the front of the class to read their story. Then the teacher gave comments and correction toward the result of their story. The teacher corrected the students’ pronunciation, choice of words, and the use of tense. In the last discussion, the teacher asked the students to take a piece of paper and gave the name of each group on it. She told the students that they would play a game. The teacher wanted to refresh the students’ mind in the end of the lesson by playing a game. The teacher asked them to make a recount text but each group could only write one sentence on each paper. Each group was asked to choose their own topic. Then each group started to write one sentence on their paper. Next, they passed the paper to another group. So, each group continued the story of other groups. The game was like a story telling sequence (ceritaberantai). The game was over when the students had created the story until re-orientation part. After all groups finished the story, they told the story in front of the class. When each group was presenting their story, all students in the class laughed because the story that they created was funny. Then the teacher gave comments and corrections toward their story. On the third meeting on November 2nd 2013, the teacher reviewed the previous explanation about recount text. She asked some questions about recount text material to the students. Since in CLT approach the language is taught in communicative way (Finocchiaro and Brumfit, 1983), the teacher tried to make the students speak up by giving them some questions then the students tried to answer them orally. After that, the teacher showed power point slides which contains story about my mother. Each slide shows a sentence which describes a mother story. After showing it, the teacher asked the students about what the power point slide tells about. So in this part, the teacher taught speaking to the students because the teacher practiced speaking with the students by asking them some questions. Then the students answered it orally. Since the goal of teaching speaking is to encourage the acquisition of communication skill and foster real communication (Murcia, 1991), so in this session, the teacher tried to make the students foster their speaking ability by speaking more in the class. Next, the teacher asked each student to re-read aloud each sentence on the power point slide. If the students made mispronunciation on their reading, the teacher would correct it. The Students’ Response toward the Implementation of Communicative Language Teaching (CLT) Approach in Teaching Speaking Recount Text When there was a question about the students’ feeling toward the teacher’s role in the class, nine students agreed that the teacher very dominated the class and there were seventeen students said that the teacher quite dominated the class. Then the rest of the students affirmed that the teacher dominated enough the class. As stated by Breen and Candlin (1980), the role of the teacher in Communicative Language Teaching is as a manager of classroom who does not dominate more in the teaching and learning process. Besides, many students said that the learning material used by the teacher was interesting for them and quite easy to be understood. Not only the learning material that was interesting for the students, but also the approach that was applied by the teacher to teach speaking recount text for them was interesting. In addition, the CLT approach which was applied could make the students active and feel brave to speak up in the class. Overall, the students agreed that the implementation of CLT approach helped them to achieve communicative competence. The Result of the Students’ Recount Speaking Task Since the students’ recount speaking task was in the form of recount monologue speech, the researcher used scoring rubric that was especially used to score monologue speech. The researcher adapted the scoring rubric of Nakamura (2005). According to Nakamura (2005), there were five criteria assessed in monologue speech. They were organization, fluency, pronunciation, vocabulary, and performance. The researcher did not forget to discuss the students’ score with the teacher before it was represented into general score. The general result of the students’ speaking task could be seen in Appendix 5. The Discussion on the Students’ Organization Based on the scoring rubric that was used by the researcher to note down the students’ speaking task result, there were many students who got an excellent level for their organization in the speech. Besides, there were only two students who got a good level for their organization. Meanwhile, there was only one student who got poor and very poor level for their organization. It means that the students could organize their speech well. The Discussion on the Students’ Fluency Fluency means natural language use occurring when a speaker engages in meaningful interaction and maintains comprehensible and ongoing communication despite limitations in his or her communicative competence (Richard, 2006). In fluency criteria, there were only four students who were considered as excellent level. These students were very fluent in delivering their speech. This means during their speech there was almost no pause. As stated by Richard (2006) that developing fluency in language use is the goal of CLT. Then there were fifteen students who were considered as good level. Meanwhile, there were seven students who got a poor level for their fluency. Then the rest students got very poor level for their fluency. The Discussion on the Students’ Pronunciation Pronunciation is one of the components that is used to score speaking. The aspect of pronunciation deals with how the speaker pronounces words in his or her speaking. In pronunciation criteria, there were only two students who were considered as excellent level. These students could pronounce every word well in their speech. Almost there was no mispronunciation in their speech. Then there were seventeen students who were considered as good level. Meanwhile, there were eight students who got a poor level for their pronunciation. Then there were only one student who got very poor level for his pronunciation. The Discussion on the Students’ Vocabulary The vocabulary deals with whether or not there is a rich variety of words that is used by the students in delivering their speaking. In vocabulary criteria, there were only four students who were considered as excellent level. These students could use many varieties of words in delivering their speech. Then there were fifteen students who were considered as good level. Meanwhile, there were eight students who got a poor level for their vocabulary. Then the rest students got very poor level for their vocabulary. The Discussion on the Students’ Performance The performance deals with how the speaker delivered their speaking. It deals with whether or not the speaker is able to speak confidently, loudly, and naturally. In performance criteria, there were fifteen students who were considered as excellent level. They could deliver confidently, naturally, and loudly. Then there were nine students who were considered as good level. Meanwhile, there were only three students who got a poor level for their performance. Then the rest students got very poor level for their performance. CONCLUSION AND SUGGESTIONS Conclusion The conclusion of this study is that Communicative Language Teaching (CLT) approach can be used as teaching approach in teaching speaking recount text to the eighth grade students of SMPN 2 Jombang. Besides, based on the result of questionnaire, most of the students said that the use of CLT approach can help them achieve the communicative competence. Besides, they also argued that the implementation of CLT approach was interesting and could make them to be more active in the class. Furthermore, the use of CLT approach could help the eighth grade students of SMPN 2 Jombang in learning speaking recount text. It is showed by the result of the students’ recount speaking task. The students’ task was in the form of recount monologue speech. They were asked to deliver a monologue speech about their unforgettable experience. The result of their speaking task showed that most of the students could speak fluently, with good organization, pronunciation, performance and also appropriate vocabulary. Suggestions Based on the data interpretation and the previous conclusion, the researcher has some suggestions for the teachers and the other researchers. In teaching speaking, the teacher should not teach the students by asking them to memorize the language but the teachers have to teach the language as the tool of communication in the class. Furthermore, the English teachers have to be creative in teaching learning process especially in teaching speaking. It means that the teachers should use the appropriate teaching approach or material that can avoid the students’ boredom and make them interested in learning speaking. DAFTAR PUSTAKA Banciu&Jireghie. (2012). Communicative Language Teaching. University of Oradea and Western University of Arad. Breen, M. P., & C. Candlin. (1980) .The essentials of A Communicative Curriculum in Language Teaching. Applied Linguistics 1(2): 89-112. Finocchiaro, M. C. &Brumfit. (1983) .The Functional National Approach: From Theory to Practice. New York: Oxford University Press. Hossen, T. M. .(2008) .Communicative Language Teaching: Teachers’ Perception in Bangladesh (Secondary Level). Bangladesh: BRAC University. Kayi, H. (2006). November.Teaching Speaking: Activities to Promote Speaking in a Second Language.The Internet TESL Journal, Vol. XII, No. 11.Retrieved January 2013, from http://iteslj.org/Techniques/Kayi-TeachingSpeaking.html. Koshy, V. (2005). Action Research for Improving Practice A Practical Guide. London: Paul Chapman Publishing. Littlewood, W. (1981).Communicative Language Teaching. Cambridge: Cambridge University Press. Mc.Millan, J. and Scumacher. (2001). Research in Education. United States: Mc.Graw Hill. Nakamura, Y. (2003). Oral Proficiency Assessment: Dialogue Test and Multilogue Test. 2003 JALT Pan- SIG Conference Proceedings. 51-61. The Japan Association for Language Teaching: Tokyo. Online Available at http://www.jalt.org/pansig/2003/HTML/Nakamura.htm Richards, C. J. & Rodgers, S. T. (1986). Approaches and Methods in Language Teaching. New York: Cambridge University Press. Richards, C. J. (2006) .Communicative Language Teaching Today. New York: Cambridge University Press. Richards, C. J. (2008). Teaching Listening and Speaking From Theory to Practice. New York: Cambridge University Press Richards, J. C. &Renandya, W. A. (2002). Methodology in Language Teaching an Anthology of Current Practice. New York: Cambridge University Press, p. 75.